Determination of the Bioactive Compounds from Echinacea purpurea (L.) Moench Leaves Extracts in Correlation with the Antimicrobial Activity and the In Vitro Wound Healing Potential - Cristina Burlou-Nagy; Florin Bănică; Rodica Anamaria Negrean; Tünde Jurca; Laura Grațiela Vicaș; Eleonora Marian; Ildikó Bácskay; Rita Kiss; Pálma Fehér; Simona Ioana Vicaș; Florina Miere (Groza); Adriana Ramona Memete; et al. (Molecules, 2023)
This study aimed at the relationship between antioxidant capacity, antimicrobial activity, and in vitro evaluation of the wound healing effect of the extract obtained from Echinaceae purpureae folium (EPF). This study’s objective was to assess the bioactive components (total phenol and flavonoid content) and antioxidant activity of EPF extracts using the DPPH test method. The antioxidant capacity and the quantities of the compounds with antioxidant capacity were evaluated by spectrophotometric methods. Antimicrobial activity has been investigated against various pathogenic microorganisms. The minimum inhibitory concentration was determined by the microdilution method. Additionally, our work used a scratch test to examine the in vitro wound healing effects of EPF extract on NHDF cells. Statistical analysis was used to quantify the rate of migration and proliferation of fibroblast cells within the wound. Microscope pictures of fibroblast cells exposed to various EPF extract dosages were processed to estimate the width of the wound, area of the wound, and cell density inside the wound. The study proved that there was a relationship between the antioxidant, antimicrobial, and wound healing ability of EPF extracts.